2012
DOI: 10.1111/j.1600-0501.2012.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus and metabolic control on bone healing around osseointegrated implants: removal torque and histomorphometric analysis in rats

Abstract: Diabetes mellitus impaired the bone healing around dental implants with established osseointegration because the results presented a lower percentage of bone area in group D in relation to groups C and I resulting in a lowest torque values for implant removal. Moreover, insulin therapy prevents the occurrence of bone abnormalities found in diabetic animals and osseointegration was not compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…We found that the diabetic state in animals determined a significant delay in the bone formation process throughout the trial period, as previously demonstrated in other studies 18 .…”
Section: Discussionsupporting
confidence: 91%
“…We found that the diabetic state in animals determined a significant delay in the bone formation process throughout the trial period, as previously demonstrated in other studies 18 .…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present observational study concur with those of several earlier studies, which demonstrated that hyperglycemic state leads to alterations in bone functions. 18,19,20,21 Other retrospective studies have also recognized pathological changes in bone function related to chronic hyperglycemia. 22,23 The present study observed that PIBL was high in T2DM patients in relation to mean HbA1c levels of 8.2%.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, sequester was not formed throughout the whole period, although the alveolar crest was in close proximity with ulcer surface at the early phase. Sequester of Group DM was heavily infected with bacterial colonies, and consequently could hardly be resorbed and isolated by surrounding inflamed granulation tissue, bringing persistent inflammation, and impaired healing 12,47,48) . Subsequently experiment 2 was carried out to examine the relation between sequester formation and large amount of bacterial deposition, where the effect of disinfection to the gingival col was challenged.…”
Section: The Measurement Of Osteoclastsmentioning
confidence: 99%